Determination of potential uses of tachuelo wood (zanthoxylum rhoifolium lam.) From the evaluation of the physical-mechanical properties and anatomical characteristics. - Aldana Amaya, Cristian David
Wood has multiple properties that are found depending on the type of species, anisotropic variation, and the anatomical and physical-chemical characteristics, which when characterizing it allows determining the potential and appropriate use for each forest species. In this way, the potential uses for Tachuelo wood (Zanthoxylum rhoifolium Lam.) Were determined, based on the anatomical characteristics and physical-mechanical properties of its wood. The anatomical characteristics were evaluated macroscopically and microscopically in the three study planes, obtaining an important relationship with the mechanical properties, additionally the physical-mechanical properties were evaluated using the standards of the Pan American Commission of Technical Standards (COPANT) and colombian technical standard (NTC), obtaining results adjusted to 12 % moisture content; its statistical analysis was performed based on the arithmetic mean and standard deviation. The results of the anatomical characteristics reveal the presence of small to medium pores, with high frequency (up to 28 pores / mm2), seriate triseriate rays, septate and thin fibers with a thickness of 2.9 µm; the physical properties reveal a basic density presents a value of 0.67 g / cm3 classified as heavy, a dimensional stability coefficient of 1.65 categorized as standard wood and a total volumetric contraction of 13.5% categorized as moderate; The mechanical properties parallel compression presented a resistance of 380.23 kg / cm2 classified as medium, perpendicular compression with a value of 149.36 kg / cm2 categorized as low and shear with 146.78 kg / cm2. Potential uses for Tachuelo wood were found to be concentrated around the construction of structures such as beams, sleepers, columns, floors, doors, tool handles, and boards.